Epilepsy in hemiplegic migraine: Genetic mutations and clinical implications. (February 2018) - Prontera, P; Sarchielli, P; Caproni, S; Bedetti, C; Cupini, LM; Calabresi, P; Costa, C
Objective: We performed a systematic review on the comorbidities of familial/sporadic hemiplegic migraine (F/SHM) with seizure/epilepsy in patients with CACNA1A, ATP1A2 or SCN1A mutations, to identify the genotypes associated and investigate for the presence of mutational hot spots. Methods: We performed a search in MEDLINE and in the Human Gene Mutation and Leiden Open Variation Databases for mutations in the CACNA1A, ATP1A2 and SCN1A genes. After having examined the clinical characteristics of the patients, we selected those having HM and seizures, febrile seizures or epilepsy. For each gene, we determined both the frequency and the positions at protein levels of these mutations, as well as the penetrance of epilepsy within families. Results: Concerning F/SHM-Epilepsy1 (F/SHME1) and F/SHME2 endophenotypes, we observed a prevalent involvement of the transmembrane domains, and a strong correlation in F/SHME1 when the positively charged amino acids were involved. The penetrance of epilepsy within the families was highest for patients carrying mutation in the CACNA1A gene (60%), and lower in those having SCN1A (33.3%) and ATP1A2 (30.9%) mutations. Conclusion: Among the HM cases with seizure/epilepsy, we observed mutational hot spots in the transmembrane domains of CACNA1A and ATP1A2 proteins. These findings could lead to a better understanding of the pathological mechanisms underlying migraine and epilepsy, therein guaranteeing the most appropriate therapeutic approach.